Intellectual property rights (IPR): what is a patent worth? - Mohd Lila, Mohd Azmi (Universiti Putra Malaysia Press, 2004)
Patents provide exclusivity for the commercialization of inventions and often play a crucial role in convincing potential investors in many industries. Patent is a kind of intangible asset and its value can be estimated using cost approach, market approach or income approach. However, the usefulness of each approach is rather situational and it demands different kinds of consideration. The value of patents shall be higher if it is packaged together with other forms of intellectual property rights. One or more patents along with other forms of IP such industrial design, trade secret or know-how are often the best proof of an entity’s ability to exclude competitors from free riding on the novel/original or aesthetically attractive features of its products or services.